THE EFFECT OF TRANSFER PRICING AND PROFIT MANAGEMENT ON TAX AVOIDANCE IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE MANUFACTURING SECTOR - Fajar Nugraha Yusman; Iqbal Pajar Sidik; Tarinih Tarinih (JASS (Journal of Accounting for Sustainable Society), 2025)
Taxes are crucial for public welfare. They serve as revenue for the state for government activities, such as infrastructure development. However, many taxpayers, including companies, still engage in tax avoidance, resulting in reduced government tax revenue. Companies can avoid excessive taxation without violating laws and regulations. One such mechanism is transfer pricing and earnings management. Therefore, this research aims to analyze the effect of transfer pricing and earnings management on tax avoidance, both partially and simultaneously. This study used a quantitative method with a sample of 12 companies listed on the Indonesia Stock Exchange (IDX) in the manufacturing sector from 2019 to 2023. The analysis showed that transfer pricing and earnings management did not significantly influence tax avoidance, either partially or simultaneously. This finding indicates that the sample companies do not utilize these two mechanisms as their primary means of tax avoidance.